The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.2478/gp-2019-0014
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety In A Dental And Maxillofacial Surgery Consulting Room: Does Previous Experience Matter?

Abstract: ObjectivesTo explore the associations between previous dental visits and dental anxiety among patients presenting at the dental and maxillofacial surgery clinic of Department of Dental and Maxillofacial Surgery, Federal Medical Centre, Birnin Kebbi, Nigeria.Materials and methodsThis study was a cross-sectional study conducted among 172 patients. Study instrument was a 9-item structured questionnaire, which obtained information about the participants regarding their: demographic profile; previous dental experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…There was a big difference between age subgroups (only 61 children of 174 at 4-6 years old), so there is no proper statistical interpretation. However, in terms of patient gender, different studies have reported that fear is greater among female patients [35,37,39], although in our series no significant correlation was found between patient gender and fear of the dentist.…”
Section: Discussioncontrasting
confidence: 87%
“…There was a big difference between age subgroups (only 61 children of 174 at 4-6 years old), so there is no proper statistical interpretation. However, in terms of patient gender, different studies have reported that fear is greater among female patients [35,37,39], although in our series no significant correlation was found between patient gender and fear of the dentist.…”
Section: Discussioncontrasting
confidence: 87%
“…In many parts of the world, including Nigeria, many people still report anxiety as a barrier to dental treatments. 10 – 16 Moreover, inadequate knowledge of dental procedures such as endodontics/root canal treatment (RCT), invariably affects the perception of individuals and the outcome of the treatment. 17 , 18 …”
Section: Introductionmentioning
confidence: 99%
“…In many parts of the world, including Nigeria, many people still report anxiety as a barrier to dental treatments. [10][11][12][13][14][15][16] Moreover, inadequate knowledge of dental procedures such as endodontics/root canal treatment (RCT), invariably affects the perception of individuals and the outcome of the treatment. 17,18 Endodontic treatment (RCT), conservative management of a complication arising from delay in accessing oral health care probably due to fear, is a fear factor by itself.…”
Section: Introductionmentioning
confidence: 99%